Competition-oriented Wage Policy and Its Effects on Aggregate Demand in the Netherlands - Stefan Ederer (Austrian Institute of Economic Research (WIFO), 2008)
This paper aims at empirically assessing the demand effects of changes in functional income distribution for the Netherlands. Based on a Neo-Kaleckian theoretical macroeconomic model, equations for the main demand aggregates (consumption, investment, exports and imports) are estimated. The effect of an increase in the wage share on these aggregates is calculated from comparative static. Alternatively, a simulation of this effect is run by means of a small macroeconomic model. An increase in the wage share would have positive effects on consumption and affects investment and net exports negatively. The overall effect is still positive; the demand regime is wage-led. A shift in income distribution from profits to wages would therefore stimulate aggregate demand. The Dutch wage policy since 1982 which aimed at restraining real wages seems to have increased international competitiveness but not aggregate demand.
Keywords: 330; consumption; distribution; demand; foreign trade; investment; Keynesian economics; macroeconomics; Lohnpolitik; Einkommensverteilung; Gesamtwirtschaftliche Nachfrage; Internationaler Wettbewerb; Postkeynesianismus; Niederlande